2014
DOI: 10.5713/ajas.2013.13314
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Sea Tangle (<italic>Laminaria japonica</italic>) and Charcoal Supplementation as Alternatives to Antibiotics on Growth Performance and Meat Quality of Ducks

Abstract: A total of 150 growing ducks were assigned to five dietary treatments to study the effect of sea tangle and charcoal (STC) supplementation on growth performance and meat characteristics in a completely randomized design. There were six replicates and five ducklings in each replication. The five dietary treatments were control, antibiotic, and 0.1%, 0.5%, and 1% STC supplemented diets. No significant differences were found on ADG, ADFI, and gain:feed among treatments in different weeks. The overall (0 to 3 week… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
32
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(37 citation statements)
references
References 24 publications
3
32
0
2
Order By: Relevance
“…For instance, it has been reported that about 500 000–700 000 tons dried L. japonica can be harvested per year from the Chinese coasts , showing it is a very rich resource. In recent decades, L. japonica has attracted great interests of chemists and pharmacologists on account of the abundance of functional components and their specific health benefits [, and .Among these functional components, we found that the crude polysaccharides extracted from L. japonica have good potential for retarding the genesis in atherosclerotic lesion via modulation of lipid metabolism in mice . However, there is still no report on the structure and mechanisms of polysaccharides with antiatherosclerosis.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, it has been reported that about 500 000–700 000 tons dried L. japonica can be harvested per year from the Chinese coasts , showing it is a very rich resource. In recent decades, L. japonica has attracted great interests of chemists and pharmacologists on account of the abundance of functional components and their specific health benefits [, and .Among these functional components, we found that the crude polysaccharides extracted from L. japonica have good potential for retarding the genesis in atherosclerotic lesion via modulation of lipid metabolism in mice . However, there is still no report on the structure and mechanisms of polysaccharides with antiatherosclerosis.…”
Section: Introductionmentioning
confidence: 99%
“…It has also been found that the omega-3 fatty acids in ducks increased when 1% wood biochar was supplemented in their feed. Islam et al (2014) found that 1% biochar in daily feed could lower LDL concentration, increase HDL concentration (p < .05) and reduce the omega-6/omega-3 polyunsaturated fatty acids ratio. They also found that adding wood biochar (0.1%, 0.5%, or 1%) to ducks' diets had no adverse effect on their overall growth performance, which was similar to that of the group given antibiotics (0.01% chlortetracycline).…”
Section: Poultry: Chicken and Ducksmentioning
confidence: 93%
“…The wood charcoal supplementation to the hens diet can help to reduce the incidence of cracked eggs through improved mineral intake from biochar, which contained high levels of ask, calcium, potassium and magnesium (Kutlu et al, 2001). It can also promote the growth and survival rate of fish (Khaki, Malcevschi, Voccia, & Marzano, 2017;Mabe et al, 2018) and promote immunity by increasing high-density lipoprotein (HDL) and decreasing low-density lipoprotein (LDL) in ducks (Islam et al, 2014). It also reduced pathogens such as Campylobacter hepaticus and Gallibacterium anatis in chickens due to its adsorption properties (Willson et al, 2019).…”
Section: Production Conditions Similaritymentioning
confidence: 99%
See 1 more Smart Citation
“…It is estimated that two-thirds of the earth’s biomass is comprised of more than 25,000 species of algae [4]. That statistic shows the potential for algae to be used as animal feed additives due to their vast biodiversity [5] and has recently been discussed as a source of bioactive compounds due to their biological properties [6,7]. Ecklonia cava ( E. cava ) is among one of the types of seaweed, which is found mainly in South Korea, Japan and China and widely used in human food because of their therapeutic effects.…”
Section: Introductionmentioning
confidence: 99%